2021
DOI: 10.3847/2041-8213/ac2f3c
|View full text |Cite|
|
Sign up to set email alerts
|

Building Better Spin Models for Merging Binary Black Holes: Evidence for Nonspinning and Rapidly Spinning Nearly Aligned Subpopulations

Abstract: Recent work paints a conflicting portrait of the distribution of black hole spins in merging binaries measured with gravitational waves. Some analyses find that a significant fraction of merging binaries contain at least one black hole with a spin tilt >90° with respect to the orbital angular momentum vector, which has been interpreted as a signature for dynamical assembly. Other analyses find that the data are consistent with a bimodal population in which some binaries contain black holes with negligible s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
157
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(180 citation statements)
references
References 56 publications
16
157
7
Order By: Relevance
“…Dynamically formed binary black holes should have isotropically oriented spin directions, while BH-BH mergers from isolated binary evolution are expected to have spins preferentially aligned with the orbital angular momentum (e.g., Farr et al 2017;Rodriguez et al 2016b). Is there already evidence for a separate population of dynamically formed systems based on spin-orbit misalignment angles (Abbott et al 2021c;Roulet et al 2021;Galaudage et al 2021)? Meanwhile, the orbits of most binary black holes are expected to circularise through gravitational-wave emission by the time they approach merger and become detectable with current instruments (Peters 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamically formed binary black holes should have isotropically oriented spin directions, while BH-BH mergers from isolated binary evolution are expected to have spins preferentially aligned with the orbital angular momentum (e.g., Farr et al 2017;Rodriguez et al 2016b). Is there already evidence for a separate population of dynamically formed systems based on spin-orbit misalignment angles (Abbott et al 2021c;Roulet et al 2021;Galaudage et al 2021)? Meanwhile, the orbits of most binary black holes are expected to circularise through gravitational-wave emission by the time they approach merger and become detectable with current instruments (Peters 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Under the current mass prior, however, which is the same uniform-indetector-masses prior used in other catalogs [3,5], the BBH solution with a secondary in the LMG and a mass ratio of ∼ 0.5 is favored over the NSBH solution with mass ratio ∼ 0.2. In either case the effective spin is positive, which (along with the masses) makes these systems feasible to produce in standard isolated binary evolution models [72,73,92]. Since the maximum NS mass is uncertain (according to Alsing et al [61] it can be constrained to [2, 2.6] M ), determining whether these are BBH or NSBH mergers may be sensitive to prior assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…The mass distribution is coupled to the spin distribution in many formation channel models (see, e.g., discussion by Mapelli [88]) -especially near mass gap edges [89] -and correlation between masses and spins has been found in the detected population [90]. Indeed, population models which allow for this mass-spin correlation are significantly better at fitting the population than models which do not [91], as are models which allow for independently modeled sub-populations [19,92]. Included in the new events reported here are examples of well-measured large effective spins in both directions (see Table I), which will improve statistics in the ongoing empirical analyses of the population's underlying spin distribution.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that a model can pass this test while still being quite badly misspecified. Abbott et al (2021d) found evidence for negatively aligned spins in a population of compact-object binaries, but this was later shown to be a model-dependent feature (Roulet et al, 2021;Galaudage et al, 2021). This test may be particularly unreliable if there is a sharp feature in the data that is not captured by the prior.…”
Section: Recommended Testsmentioning
confidence: 99%